ARF Impedes NPM/B23 Shuttling in an Mdm2-Sensitive Tumor Suppressor Pathway - Brady, Suzanne N. (American Society for Microbiology, 2004)
The ARF tumor suppressor is widely regarded as an upstream activator of p53-dependent growth arrest and apoptosis. However, recent findings indicate that ARF can also regulate the cell cycle in the absence of p53. In search of p53-independent ARF targets, we isolated nucleophosmin (NPM/B23), a protein we show is required for proliferation, as a novel ARF binding protein. In response to hyperproliferative signals, ARF is upregulated, resulting in the nucleolar retention of NPM and concomitant cell cycle arrest. The Mdm2 oncogene outcompetes NPM/B23 for ARF binding, and introduction of Mdm2 reverses ARF's p53-independent properties: in vitro, NPM is released from ARF-containing protein complexes, and in vivo S phase progression ensues. ARF induction by oncogenes or replicative senescence does not alter NPM/B23 protein levels but rather prevents its nucleocytoplasmic shuttling without inhibiting rRNA processing. By actively sequestering NPM in the nucleolus, ARF utilizes an additional mechanism of tumor suppression, one that is readily antagonized by Mdm2.